Epistemologi Inkar Al-Sunnah: Telaah Pemikiran Kassim Ahmad - Benny Afwadzi (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2018)
This article analyzes the epistemology of the inkar al-sunnah (sunnah pengingkar), which specializes in the study of Kassim Ahmad, a Malaysian Malaysian thinker. Epistemologically, he rejects the existence of the hadith of the Prophet with three sources of knowledge, namely empirical, rational, and revelation. But unfortunately, even though he was passionate about "exposing" the problems surrounding the hadith, it was unexpected in his conclusions he stated that he still accepted the hadith if it was in accordance with the content of the Koran. This view also seemed to sink into the vast sea of ​​his rejection of hadith. This is the thing that feels ambiguous in Kassim's thinking. Furthermore, when examined in depth, Kassim's thoughts related to the placement of hadith are in the position of absolute inkar al-sunnah or with other perspectives categorized as inkar al-sunnah juz'i.